Inclusive Entrepreneurial Training for Women, Small Farmers, and Disabled People in Kupang, East Nusa Tenggara - Basbeth, Firdaus (Journal of Sustainable Community Development (JSCD), 2025)
This community development paper is related to socioeconomic issues in East Nusa Tenggara (NTT), an area known for its high rates of poverty and child malnutrition. Wahana Visi Indonesia launched an Inclusion Community Development Program to empower underprivileged households and small farmers in response to these issues, working with the PPM School of Management. Workshops that promoted opportunity recognition, business planning, and digital marketing were used to help participants develop their entrepreneurial abilities during the February 2025 event. Explanation, coaching and mini case studies are a technique used in community development to comprehend and resolve issues.. The results show that despite efforts to include underrepresented groups, participants' understanding of entrepreneurial principles was hindered by educational gaps. By highlighting the value of cooperatives and ongoing training for sustainable economic growth in NTT, the program showed promise for fostering resilience and inventiveness in local economies. Suggestions for upcoming projects include continued assistance for collaborative growth and customized instruction to improve participants' business savvy